Room temperature synthesis of TiO2 supported chitosan photocatalyst: Study on physicochemical and adsorption photo-decolorization properties. (February 2017) - Afzal, Saba; Samsudin, Emy Marlina; Mun, Lee Kian; Julkapli, Nurhidayatullaili Muhd; Hamid, Sharifah Bee Abd
Graphical abstract: Highlights: Room temperature modification of TiO2 with CS. Impact of CS on charge carrier recombination rate. Decline in adsorption-photodecolorization property with calcination treatment. Abstract: The room temperature in-situ sol gel technique was used to synthesize TiO2 supported chitosan (CS) nanocomposites. The effect of calcination was assessed in the context of its physicochemical and adsorption-photodecolorization properties. During sol gel, hydrolysis and condensation of titanium alkoxide was conducted under acidic conditions, which resulted in the formation of crystalline anatase phase in TiO2 -CS (TC) composite at room temperature. Furthermore, calcination treatments (100 °C, 300 °C, 500 °C) gradually increased the charge carrier recombination rates, due to the thermal degradation of Chitosan. Photocatalytic activity was assessed using Methyl orange, which resulted in 100% decolorization within 90 min of UV exposure with un-calcined nanocomposite. Hence, the reactive OH and NH2 functional groups on the surface of CS are responsible for the adsorption-photodecolorization process. Overall, this study provides comprehensive data on the effective modification of TiO2 with Chitosan and the effect of calcination on the physicochemical and adsorption-photodecolorization properties of the TC nanocomposite.